Pharmacological modulation of endogenous opioid activity to attenuate neuropathic pain in rats - Liu, Nai-Jiang (J Pain, 2018)
We previously showed that spinal mGluR(1) signaling suppresses or facilitates (depending on stage of estrous cycle) analgesic responsiveness to intrathecal endomorphin 2 (EM2), a highly mu-opioid receptor (MOR)-selective endogenous opioid. Spinal EM2 antinociception is suppressed during diestrus by mGluR(1) when it is activated by membrane estrogen receptor alpha (mERα), and facilitated during proestrus when mGluR(1) is activated by glutamate. In the current study, we tested the hypothesis that in female rats subjected to spinal nerve ligation (SNL), inhibition of spinal estrogen synthesis or blockade of spinal mERα/mGluR(1) would be anti-allodynic during diestrus, whereas during proestrus mGluR(1) blockade would worsen the mechanical allodynia. As postulated, following SNL, aromatase inhibition or mERα/mGluR(1) blockade during diestrus markedly lessened mechanical allodynia. This was observed only on the paw ipsilateral to SNL and was eliminated by naloxone, implicating endogenous opioid mediation. In contrast, during proestrus, mGluR(1) blockade worsened SNL-induced mechanical allodynia of the ipsilateral paw. Findings suggest menstrual cycle stage-specific drug targets for and the putative clinical utility of harnessing endogenous opioids for chronic pain management in women, as well as the value of, if not the necessity for, considering menstrual cycle stage in clinical trials thereof.